Effects of fan speed on spray deposition and drift for targeting air-assisted sprayer in pear orchard - Wei, Qiu; Sanqin, Zhao; Weimin, Ding; Chengda, Sun; Jiang, Lu; Yinian, Li; Jiabing, Gu (International Journal of Agricultural and Biological Engineering, 2016)
In order to reduce the application dosage of pesticides, a targeting air-assisted (TAA) sprayer was developed and tested in this study. Fruit trees were assayed by an infrared detection system to determine if the canopy needs to be sprayed. This TAA sprayer was compared with conventional air-assisted (CAA) sprayers, and the impacts of various fan speeds (0, 800 r/min, 1300 r/min, and 1800 r/min) on spray deposition, coverage, and drift amount were tested. Ponceau 2R was used as tracer to measure spray deposition under each treatment. Droplet coverage and canopy deposition were best when the CAA application fan speed was increased to 1300 r/min, but at higher fan speeds, spray deposition and coverage in canopy did not increase because extra air flow blew droplets from the ground into the air. During TAA spraying, droplet sizes increased at opening and closing moments. Optimal spray effects were achieved when the auxiliary airflow velocity was increased at a fan speed of 1800 r/min. The research provides a useful reference for the design of TAA and parameters optimization method with respect to the relationship between droplets deposition into tree canopy, ground and drift in the air.Keywords: sprayers, infrared detectors, spray deposition, drift, fruit trees, plant protectionDOI: 10.3965/j.ijabe.20160904.1938Citation: Qiu W, Zhao S Q, Ding W M, Sun C D, Lu J, Li Y N, et al. Effects of fan speed on spray deposition and drift for targeting air-assisted sprayer in pear orchard. Int J Agric & Biol Eng, 2016; 9(4): 53－62.